Organic chemistry : 100 must-know mechanisms - Valiulin, Roman A. (Berlin ; Boston : Walter de Gruyter GmbH, 2020)
'This book summarizes 100 essential mechanisms in organic chemistry ranging from classical such as the Reformatsky Reaction from 1887 to recently elucidated mechanism such as the copper(I)-catalyzed alkyne-azide cycloaddition. The reactions are easy to grasp, well-illustrated and underpinned with explanations and additional information.'
Includes bibliographical references.
Keywords: Chemistry, Organic; Reaction mechanisms (Chemistry)